2009
DOI: 10.2514/1.43657
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Microwave-Generated Plasma with a Hemisphere Cylinder at Mach 2.1

Abstract: Microwave energy deposition is a novel method for flow control in high-speed flows. Experiments have demonstrated its capability for beneficial flowfield modification in supersonic flow including, for example, drag reduction for blunt bodies. A fully three-dimensional, time-accurate gas dynamic code has been developed for simulating microwave energy deposition in air and the interaction of the microwave-generated plasma with the supersonic flow past a blunt body. The thermochemistry model includes 23 species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…130 The thermochemistry model also allows the gas processes which result in the rapid heating to be better understood. The findings of Knight et al, 143 as shown in Figure 55, validated against experimental results show that this type of model can accurately model the impact of microwave energy deposition on high speed flows. The same model is used in a study by Knight et al 123 in an effort to replicate the experimental results of Kolesnichenko et al 122 The minimum achieved surface pressure of the numerical model showed excellent comparison to the experimental data, however the duration of this feature was debated.…”
Section: Numerical Modelling Of Microwave Dischargesmentioning
confidence: 67%
See 1 more Smart Citation
“…130 The thermochemistry model also allows the gas processes which result in the rapid heating to be better understood. The findings of Knight et al, 143 as shown in Figure 55, validated against experimental results show that this type of model can accurately model the impact of microwave energy deposition on high speed flows. The same model is used in a study by Knight et al 123 in an effort to replicate the experimental results of Kolesnichenko et al 122 The minimum achieved surface pressure of the numerical model showed excellent comparison to the experimental data, however the duration of this feature was debated.…”
Section: Numerical Modelling Of Microwave Dischargesmentioning
confidence: 67%
“…So in effect, the ideal gas simulations are defining inputs based on previous experimental conditions rather than using the actual energy deposition input parameters themselves. 143 This would seem to indicate that the ideal gas simulations, although useful for the general study of microwave energy deposition, are somewhat limited by their inputs.…”
Section: Numerical Modelling Of Microwave Dischargesmentioning
confidence: 99%
“…The latter effect was named the vortex drag reduction. The reduction of drag force together with the decrease of the stagnation parameters was obtained experimentally and numerically for air, in particular, in [9][10][11]. Effects of a local heating on wave drag reduction were investigated in [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the problems being discussed, changing the structures of the triple-shock configurations connected with physical-chemical transformations and characteristics of an energy source define a significant modification of dynamical and heat loadings on an AD body [9,10]. For strong shock waves when physicochemical reactions occur behind the shock fronts, the self-similarity assumption does not hold true because of relaxation effects.…”
Section: Introductionmentioning
confidence: 99%
“…The inelastic collisions provide energy transfer through several di¨erent mechanisms including rotational excitation, vibrational excitation, excitation of electronic states, dissociations, and ionizations. The three main kinetic paths for energy transfer from these modes to the kinetic energy of the heavy particles (i. e., increasing the gas temperature) are rotational excitation, collisional quenching of the excited states, and electronion recombination [12].…”
Section: Laser and Microwave Discharge In Airmentioning
confidence: 99%